Design, Implementation and Evaluation of a Data-Driven Learning Didactic Unit Based on an Online Series Corpus - Poblete-Bravo, J; Singer-Contreras, N (Universidad Catolica Silva Henriquez, 2021)
This paper presents the implementation of a didactic unit based on Singer s proposal for data-driven learning (DDL) within a task-based (TB) framework in the context of Chilean translation education. The didactic intervention has four stages: 1) data collection from students preferred multimodal consumption in order to generate a written corpus based on the transcription of popular online TV series; 2) the design of a didactic unit that graduates concordance software use and student autonomy by means of linguistic tasks; 3) the application of the approach in an English Language 7 course unit with 24 participants at the Translation Studies undergraduate program at Universidad de Santiago de Chile, and 4) the evaluation of the intervention by means of an online questionnaire. Students and lecturers perceptions suggest that a DDL-TB approach is suitable for language teaching in translator education. Further recommendations to improve future DDL-TB projects are also provided. © 2021 Universidad Catolica Silva Henriquez. All rights reserved.